3‐D Atmospheric Modeling of the Global Budget of N2O and Its Isotopologues for 1980–2019: The Impact of Anthropogenic Emissions. Issue 7 (4th July 2022) - Liang, Qing; Nevison, Cynthia; Dlugokencky, Ed; Hall, Bradley D.; Dutton, Geoff
Abstract: Nitrous oxide (N2 O) is the third most important anthropogenic greenhouse gas and a major ozone‐depleting substance. Its main sources include anthropogenic activities (mostly agriculture) and natural emissions from ocean and soils. However, emission estimates for individual sources are highly variable due to uncertainties in N2 O lifetime estimates and partitioning among sources. We derive annual global N2 O emissions for 1990–2019 using NOAA Global Monitoring Laboratory (GML) surface N2 O observations and the N2 O lifetime calculated in the NASA GEOS‐5 chemistry climate model. The inferred global mean N2 O emissions has gradually increased from ∼15.8 TgN/yr in the early 1990s to ∼17.8 TgN/yr in the 2010s. This implies that anthropogenic N2 O emissions have grown rapidly from ∼6.7 TgN/yr in the 1990s to about ∼8.7 TgN/yr in the 2010s, a ∼30% increase. With specially designed N2 O isotopic tracers in 3‐D GEOSCCM, we estimate that, on global average, stratospheric enrichment contributes about +7.7‰/yr, +7.6‰/yr, +8.0‰/yr to tropospheric δ 15 N α, δ 15 N β, and δ 18 O budget, respectively. To balance the global mean isotopic signature for pre‐industrial terrestrial sources of δ 15 N α ∼ 6.7‰, δ 15 N β ∼ −12.6‰, δ 18 O ∼ 35.4‰, our 3‐dimensional isotopic budget simulation using the GEOSCCM suggests global mean anthropogenic isotopic signatures in the recent decades are δ 15 N α ∼ −18‰, δ 15 N β ∼ −20‰, δ 18 O ∼ 19‰. These anthropogenic isotopic estimates are significantly lighter than results from one‐box atmospheric model‐based estimates with the largest difference seen for δ 15 N β . More surface isotopic measurements are needed to better quantify the N2 O isotopic signatures. Plain Language Summary: Nitrous oxide (N2 O) is a trace gas that plays an important role in Earth's atmosphere, impacting the chemical composition and radiation budget. In pre‐industrial time, N2 O in the atmosphere primarily comes from ocean and soil emissions. Atmospheric N2 O level has increased by about 20% since mid 1800s as a result of human activities, mostly agriculture. Its growth rate in recent decades has been notably greater than before. Using a 3‐Dimensional Chemistry Climate Model, we were able to determine that the notable increase in N2 O growth rate is a result of rapidly growing anthropogenic emissions started in the mid‐1990s. In addition to the atmospheric mass balance budget of N2 O, we were also able to complete a full 3‐Dimensional isotopic budget of 15 N and 18 O isotopologues for N2 O for 2000‐2019 and estimated the contribution of isotopically‐heavy stratospheric enrichment and isotopically‐light anthropogenic sources. The increase in recent anthropogenic emissions has introduced detectable changes in the observed isotopic trends. Key Points: Global Nitrous oxide emissions increased from ∼15.8 TgN/yr from the early 1990s to ∼17.8 TgN/yr in the 2010s due to increasing anthropogenic sources Stratospheric enrichment contributes about +7.7‰/yr, +7.6‰/yr, +8.0‰/yr to the tropospheric δ 15 N α, δ 15 N β, and δ 18 O budget The 3‐dimensional model estimated global mean isotopic signatures for anthropogenic sources are δ 15 N−α ∼ −18‰, δ 15 N−β ∼ −20‰, and δ 18 O ∼ 19‰